REGENERASI ULAMA MELALUI MODERNISASI PESANTREN: STRATEGI PENDIDIKAN DAN HUKUM ISLAM DALAM PERSPEKTIF SEJARAH, SOSIAL, DAN POLITIK - Ronika Putra; Saifullah; Julhadi; Tamrin Kamal; Desi Asmaret (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of pesantren in regenerating ulama through modernization, as well as the educational strategies and Islamic law applied in the historical, social, and political contexts. Using a qualitative approach with a case study method, this research examines pesantren that adopt modernization in curriculum and management. The results showed that pesantren succeeded in modernizing education without sacrificing traditional values, producing ulama who are adaptive to the times. This study concludes that the regeneration of ulama through modernization of pesantren is very relevant to produce competent ulama in the global era, while still maintaining the authenticity of tradition. Further research is recommended to analyze the impact of modernization on the authority of the ulama and the effectiveness of the use of technology in pesantren education.